Cytomegalovirus Infection following Kidney Transplantation: a Multicenter Study of 3065 Cases - Einollahi, B. (Avicenna Organ Transplantation Institute, 2012)
Background: Cytomegalovirus (CMV) infection is a common complication following kidney transplantation. Objective: To assess the incidence and risk factors of CMV infection among renal transplant recipients. Methods: In a retrospective multicenter study, 3065 renal transplant recipients from 17 transplant centers of Iran were studied between April 2008 and January 2011. Kidney transplant patients were routinely monitored by sequential blood samples drawn for use in the CMV-pp65 antigenemia assay, and for hematological and biochemistry tests. Results: 63% of studied patients were males; the mean±SD age of participants was 38±15 years. The majority of cases (81%) received a kidney from a living unrelated donor (LURD), 9% from living related donor (LRD), and 10% from deceased donors. 671 patients experienced CMV viremia. The incidence of CMV infection was 21.9% (95% CI: 20.4%–23.4%). The rate was higher in the first 6 months after transplantation (p<0.001); in recipients with higher level of cyclosporine (p<0.001); in those with lower hemoglobin concentration (p=0.02); patients with elevated ALT (p<0.001); those with increased fasting blood sugar (p=0.005); recipients with dyslipidemia (p<0.05); deceased kidney recipients (p=0.006); and patients with kidney graft impairment (p=0.01). In multivariate regression analysis, time since kidney transplantation (p<0.001) and renal allograft failure (p<0.001) were the only risk factors associated with CMV infection. Conclusions: CMV infection was a common complication in the first 6 months of kidney transplantation, particularly among patients with kidney graft impairment.